(untitled) (MAUSAM, 2009)
This paper describes the basic features of storm surge phenomena using Indian Institute of Technology (IIT) model (installed at Bangladesh Meteorological Department) for the Bay of Bengal. To capture the storm surge scenarios, after the entrance of the cyclone into the northern part of the Bay of Bengal, high resolution IIT model has been used. The analysis area is from 18° N to 23° N and 83.5° E to 94.5° E. Bathymetric data required for the model has been taken from Royal Admiralty Table and ETOPO2 dataset. In this paper, various scenarios of storm surges are developed and then investigated for varying input parameter values. This paper also examines the time-series of surges at the fixed landfall point by using the data of three severe cyclonic storms when the cyclone approaches the landfall point.